Comparison of Oral Loading Dose to Intravenous Acetaminophen in Children for Analgesia After Tonsillectomy and Adenoidectomy: A Randomized Clinical Trial. (23rd July 2021) - Lammers, Cathy R.; Schwinghammer, Amy J.; Hall, Brent; Kriss, Robert Scott; Aizenberg, Debbie A.; Funamura, Jamie L.; Senders, Craig W.; Nittur, Vinay; Applegate, Richard L.
Abstract : BACKGROUND: Acetaminophen is a frequently used adjunct analgesic in pediatric patients undergoing tonsillectomy and adenoidectomy. We compared opioid administration following preoperative intravenous (IV) or oral acetaminophen in addition to a standard multimodal regimen to test the hypothesis that 1 loading dose approach would provide superior opioid sparing effects among pediatric surgical patients undergoing tonsillectomy and adenoidectomy. METHODS: This single-center, double-blind, double-dummy prospective randomized study was conducted in patients ages 3 to 15 years undergoing tonsillectomy and adenoidectomy with or without myringotomy and tube placement between September 2017 and July 2019. Subjects received 1 dose of either oral acetaminophen 30 mg/kg with IV placebo (oral group) or IV acetaminophen 15 mg/kg with oral placebo (IV group). Acetaminophen plasma levels were measured at 2 timepoints to evaluate safety and determine plasma levels attained by each dosing regimen. Intraoperative opioid administration and postoperative analgesia were standardized. Standardized postoperative multimodal analgesia included opioid if needed to control pain assessed by standardized validated pediatric pain scales. The primary outcome measure was total opioid administration in the first 24 hours after surgery. Continuous data were not normally distributed and were analyzed using the Wilcoxon rank sum test and the Hodges-Lehman estimator of the median difference. Clinical significance was defined as a 100 µg/kg IV morphine equivalents per day difference. RESULTS: Sixty-six subjects were randomized into and completed the study (29 women, 37 men; age 5.9 ± 3.0 years; percentile weight for age 49.5 ± 30.2; no differences between groups). There was no opioid dose difference between oral (median 147.6; interquartile range [IQR], 119.6–193.0 µg/kg) and IV groups (median 125.4; IQR, 102.8–150.9 µg/kg; median difference 21.3; 95% confidence interval [CI] −2.5 to 44.2 µg/kg IV morphine equivalents; P = .13). No acetaminophen levels exceeded the predefined safety threshold (40 mg/L). No difference was found in the percentage of patients with severe pain: 50.0% oral group, 47.2% IV group; relative risk of severe pain in IV 0.94; 95% CI, 0.57–1.6; P = .82. Postoperative plasma acetaminophen levels were higher in oral (22; IQR, 16–28 mg/L) than IV (20; IQR, 17–22 mg/L) group (median difference 7.0; 4.0–8.0 mg/L; P = .0001). CONCLUSIONS: Opioid-sparing effects did not differ following an oral or standard IV acetaminophen loading dose with no identified acetaminophen toxicity in pediatric patients undergoing tonsillectomy and adenoidectomy who received standardized multimodal postoperative analgesia. An oral loading dose may provide more consistent serum acetaminophen levels at lower cost compared to a standard IV dose.